2016
DOI: 10.20525/ijrbs.v5i6.539
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Perceived Risk and Website Reputation on Purchase Intention

Abstract: Success in electronic commerce relies greatly on customer's trust. While other studies have examined various factors affecting the online trust, a few have researched on the joint effects of perceived risk and website reputation on purchase intention using online trust as a mediator. The current study attempts to fill the gap. 300 samples of online shoppers participated in web-based questionnaires using a quota sampling technique. Based on the confirmatory factor analysis (CFA), the measurement is valid and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
2
5
0
4
Order By: Relevance
“…It could be seen from the pvalue of both variables which had values less than 0.05 (0.0019 and 0.0017). This was in line with studies conducted by [30] [12]…”
Section: H the Indirect Effect Of Perceived Reputation And Risk On Psupporting
confidence: 93%
“…It could be seen from the pvalue of both variables which had values less than 0.05 (0.0019 and 0.0017). This was in line with studies conducted by [30] [12]…”
Section: H the Indirect Effect Of Perceived Reputation And Risk On Psupporting
confidence: 93%
“…Selain website quality, purchase intention juga dipengaruhi oleh website reputation. Website reputation adalah persepsi positif konsumen terhadap sebuah website yang dihasilkan dari pengalaman konsumen dalam menggunakan website tersebut (Tangmanee & Rawsena, 2016). Website dengan reputasi yang baik akan mendorong konsumen untuk berbelanja pada website tersebut (Tangmanee & Rawsena, 2016;Kim & Lennon, 2013).…”
Section: Pendahuluan Latar Belakangunclassified
“…Website reputation adalah persepsi positif konsumen terhadap sebuah website yang dihasilkan dari pengalaman konsumen dalam menggunakan website tersebut (Tangmanee & Rawsena, 2016). Website dengan reputasi yang baik akan mendorong konsumen untuk berbelanja pada website tersebut (Tangmanee & Rawsena, 2016;Kim & Lennon, 2013). Purchase intention juga dipengaruhi oleh persepsi risiko konsumen terhadap website yang dikunjunginya.…”
Section: Pendahuluan Latar Belakangunclassified
See 1 more Smart Citation
“…The basic theory of Kotler and Keller (2016: 195) which states that the buying decision-making process is based on cognitive and emotional influences should be expanded and more contextualized to the online environment. In addition, a study by Tangmanee and Rawsena (2016) found that trust is the key factor in e-commerce. Specific studies that focus on e-marketplace by Sfenrianto et al (2018) found that trust is one of the important factors and Prihastomo et al's (2018) mentions trust as the most important factor of the e-marketplace.…”
Section: Introductionmentioning
confidence: 99%